Systematic Literature Review : Pengaruh E-Wallet pada Perubahan Pola Konsumsi Masyarakat Perkotaan: Systematic Literature Review: The Influence of E-Wallets on Changes in Urban Consumption Patterns - Fatikha Ibnu Salma, Fatikha; Farah Safitri, Dewi; Firna Wardani, Naswa; Rahma Yunita, Sri; Roestam Afandi, Muhammad (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2026)
The advancement of financial technology, particularly the widespread use of e-wallets and digital payment systems, has considerably reshaped consumption habits within urban communities, especially among university students. Evidence from prior research highlights that ease of access, rapid transactions, and promotional incentives such as discounts, cashback, and pay-later services play a central role in driving consumptive tendencies. Hasibuan et al. (2025) reported that students prefer digital transactions over cash for convenience, while Kusuma (2020) confirmed the significant effect of e-wallet usage on student spending behavior at Raharja University. Wardani et al. (2025) further revealed that e-wallet adoption explains 38% of consumptive behavior among Generation Z students. On a broader scale, Afrizal & Megananda (2025) observed that digital payments foster a shift towards a convenience-driven lifestyle in urban areas efficient but highly susceptible to impulsive purchases and overspending. Collectively, these findings underline the importance of digital financial literacy in ensuring that the benefits of payment efficiency do not escalate into excessive consumerism.